Organizational citizenship behavior: adaptation and validation of the OCB scale CCOE-R - Paula C. Neves; Paula C. Neves; Ana Palma-Moreira; Ana Palma-Moreira; Cláudia Andrade; Cláudia Andrade; Manuel Au-Yong-Oliveira; Manuel Au-Yong-Oliveira; Manuel Au-Yong-Oliveira (Frontiers in Psychology)
IntroductionOrganizational Citizenship Behavior has evolved as a pivotal concept in organizational behavior because of its importance on fostering the success of organizations. Despite its recognized benefits, OCB’s dimensions are not consensual in literature. The goal of this paper was to adapt and validated to be used in a broader work context an OCB scale (CCOE-R) initially developed for the Portuguese specific professional context, schools and the education sector.MethodsThe sample of this study is composed of 740 participants. To validate the scale, an exploratory and a confirmatory factor analysis and scale invariance test were performed.ResultsExploratory and confirmatory factor analyses revealed a 10-item unidimensional structure, with excellent reliability indices, and goodness of fit, besides invariance for group status (managerial and non-managerial positions).DiscussionThe OCB-G (Global OCB) emerges as a reliable and valid instrument that is based on a conception of OCB as a unidimensional construct. Because the items are group referenced items, it is possible to obtain a global value of OCB that represents group perceptions on OCB, allowing research to be carried out at the group/organizational level. The (CCOE-R) is an essential contribution to the study of organizational behavior, serving as a practical tool for assessing OCB-G as it plays a prominent role in organizations.